Peran Pendidikan Agama Kristen dalam Toleransi Beragama - Yulius Unsong (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2023)
The diversity, including religious diversity, in Indonesia is an undeniable reality. As a system of beliefs and a religious system, religion plays a crucial role in creating a just and civilized way of life for all humanity in the world. Throughout the journey of mankind, religions have been an ever-flowing source of motivation and inspiration, and they will continue to evolve alongside human development. This article discusses the importance of building religious tolerance through Christian education, focusing on the correct perspective towards every religious practitioner and the Christian way of life in relation to other religious communities.The research methodology employed is descriptive. Through a deep understanding of the values of tolerance embedded in the Bible, this article explores the definition of tolerance, the perspectives of Biblical figures on religious plurality, the implementation of tolerance within various religions, factors contributing to intolerance, and efforts towards sustainable development of tolerance.